Calappoidea and Leucosioidea (Crustacea: Decapoda: Brachyura) from Luzon, Philippines, with descriptions of two new species of Mursia - Galil, Bella S.; Ng, Peter K. L. (Zootaxa, 2009)
Twenty-two species of calappoid and leucosioid crabs were identified among the material collected off Aurora Province, western coast of Luzon, Philippines, in 1987. This includes two new species of calappids, Mursia aurorae n. sp., and M. steinhardti n. sp. Two leucosioid species are new records for the Philippines: Iphiculus convexus Ihle, 1918 (Iphiculidae), and Myra digitata Galil, 2004 (Leucosiidae).